A STUDY OF TEACHING AND LEARNING APPROACHES FOR CHILDREN AT TASKA SAN LORENZO CYBERJAYA: INTERVIEW STUDIES - NURUL FATIHAH JALALLUDIN; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
This study examines the implementation of a learning approach in a nursery school that uses Montessori principles for infants and children under four years of age. The objective of the study is to identify teaching approaches, teacher challenges, and effective strategies in implementing learning. Findings show that a child-centered approach and ongoing communication with parents through annual meetings and the “Communication Link” book help children’s holistic development. Teachers face behavioral management challenges but use strategies for repeating instructions and activities tailored to individual observations. The study also emphasizes the importance of safety and hygiene in the learning environment. Recommendations include the use of technology to strengthen communication and continuity of activities at home. This study contributes to improving the quality of early education based on Montessori principles in nursery schools.